The Effect of Distributive Justice and Procedural Justice on Turnover Intention Mediated By Job Satisfaction (A Study on Pt Konishi Lemindo Indonesi) - Jourta Christian Alfano (Eduvest - Journal of Universal Studies, 2024)
This study aims to analyze the influence of distributive justice and procedural justice on employee turnover intentions at PT Konishi Lemindo Indonesia, with job satisfaction as an intervening variable. In the era of globalization, human resources are an important factor in the sustainability of the company. High employee turnover rates can result in losses for the company, so it is important to understand the factors that affect turnover intentions. This study uses a quantitative approach with primary data obtained from questionnaires. The results of the study show that distributive justice and procedural justice have a significant effect on job satisfaction, which in turn has an impact on employee turnover intentions. This research provides important insights for company management to increase job satisfaction and reduce employee turnover through the application of the principles of fairness in the organization.